170 Microfluidics cell squeezing enables potent cellular vaccines in murine models through direct cytosolic loading and direct CD8 T cell priming. (9th November 2020) - Ozay, Emrah; Booty, Matthew; Blagovic, Katarina; Soto, David; Pryor, Olivia; Stockmann, Adam; Subramanya, Disha; Volk, Kelly; Sharei, Armon; Bernstein, Howard; Yarar, Defne; Seidl, Katherine; et al.
Abstract : Background: The presentation of sufficient antigen on major histocompatibility complex class I (MHC-I) is essential to prime CD8+ T cells. Methods: To achieve efficient MHC-I presentation, we used microfluidics cell squeezing (Cell Squeeze®) to deliver antigens directly to the cytosol of antigen presenting cells (APCs), bypassing the need for cross-presentation. In addition to facilitating priming by professional APCs, this approach enables lymphocytic subsets within peripheral blood mononuclear cells (PBMCs) to function as unconventional APCs in mouse preclinical models. Results: We demonstrated that microfluidic cell squeezing delivers cargo to major cell populations within splenocytes (T cells, B cells, NK cells, and monocytes) and that protein, peptide, or mRNA antigens are rapidly processed and presented. In vivo, squeezed splenocytes directly presented antigen to CD8+ T cells. In the TC-1 tumor model for HPV+ cancers, squeezed splenocytes completely protect mice when administered prophylactically, protecting 15/15 animals from primary challenge and 11/15 animals from tumor re-challenge. Following therapeutic administration, squeezed splenocytes significantly improved median survival time to 56 days from 28 days, as observed with untreated controls. Immunization can also be combined with chemotherapy to further enhance therapeutic efficacy, improving median survival to over 100 days compared to 81 days with SQZ monotherapy or 32 days with chemotherapy alone. When tumor infiltrating lymphocytes (TILs) were analyzed following therapeutic immunization, squeezed splenocyte immunization elicited a significant influx of antigen specific CD8+ T cells: with SQZ treatment, 87% of tumor-infiltrating CD8 T cells were antigen-specific, as measured by an E7-tetramer stain, while only 33.6% and 1.15% of infiltrating CD8 T cells were specific for E7 with subcutaneous peptide vaccination and no treatment, respectively. Conclusions: Through the direct cytosolic delivery of antigen, we have engineered unfractionated PBMCs to function as potent APCs. This strategy generates potent antigen-specific CD8+ T cell responses in mouse models. Taken together, these findings support the potential of SQZ-PBMCs as an effective antigen-specific vaccination strategy against cancer. SQZ-PBMC-HPV is currently under clinical evaluation for HPV16+ tumor indications. Ethics Approval: All methods were performed in accordance with relevant guidelines and regulations; Animal studies were approved by the Institutional Animal Care and Use Committee (IACUC) at SQZ Biotechnologies, using the recommendations from the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health and the Office of Laboratory Animal Welfare. All activities were also conducted in accordance with Public Health Service (PHS) Policy on Humane Use and Care of Laboratory Animals.